Topological Transport in a Nanoscale Optomechanical Array - Marquardt, Florian (International Conference on Metamaterials, Photonic Crystals and Plasmonics, 2023)
I will present the results of a recent theory-experiment collaboration with the lab of Oskar Painter at Caltech [Nat. Comms, 13, 3476 (2022)]. We were able to design and realize the largest optomechanical array to date, using a new concept that we term a multiscale optomechanical crystal. We engineered it to produce a phononic topological metamaterial at the nanoscale, exploiting the Valley Hall effect. Thanks to the sensitivity of optomechanical measurements, we were able, for the first time, to measure the topologically protected transport of thermal excitations. This experiment paves the way towards unlocking the full toolbox of optomechanics for the field of nanoscale topological phonon transport.
CRIS-Team Scopus Importer:2024-12-16